Investigation of the role of bridge resource management on safety of navigation using by 5 WHY analysis and fishbone diagram - Dal, Almila; Kodak, Gizem (Kyrenia: University of Kyrenia, 2024)
Abstract INVESTIGATION OF THE ROLE OF BRIDGE RESOURCE MANAGEMENT ON SAFETY OF NAVIGATION USING BY 5 WHY ANALYSIS AND FISHBONE DIAGRAM Maritime transport, which makes the intercontinental trade possible, provides various advantages, both in terms of the unit cost of the cargo carried and the capacity to carry much more cargo at a time compared to other transportation systems. With this, heavy maritime traffic formed, brings with it the dangers of loss of life, environmental pollution and material damage by also increasing the accident risk. Especially in narrow canals and waterways this risk increases, and it becomes important to develop measures to strengthen safety of navigation. At this point, examining the past accidents scientifically and the analysing the characteristics of them play a key role in the development of effective measures that can prevent potential accidents with a similar profile. In this study, the impact of bridge resource management on the safety of navigation is investigated with root cause analysis by the M/V VITASPIRIT accident which took place in the Strait of İstanbul. Within the scope of the research, a 5 why analysis followed by a fishbone diagram was applied and the results obtained were evaluated with SWOT analysis. The aim is that the results obtained both visually schematize the root causes of accident and integrate them into a cause-effect relationship and thus serve as a reference for decision-makers to prevent accidents with a similar profile. Keywords: bridge resource management (BRM), safety of navigation, root cause analysis, 5 why analysis, fishbone diagram, swot analysis.
Master (Thesis)
Includes references (40-48 p.)
Text in English.
Keywords: Bridge Resource Management; Safety